2015
DOI: 10.2146/ajhp140175
|View full text |Cite
|
Sign up to set email alerts
|

Use of Twitter at a major national pharmacy conference

Abstract: The majority of MCM-related tweets by onsite and remote Twitter users were social in nature or pertained to educational sessions held over the course of the conference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 11 publications
1
21
0
1
Order By: Relevance
“…Of the 1500 public health professionals and students attended the 7 th EPH Conference in Glasgow, only 14% (209 attendees) were us Twitter Contributors (TC) that used #ephglasgow hashtag. In another study the proportion of attendees among TC was similarly high, as reported by Awad and Cocchio in a paper about the use of Twitter at a major national pharmacy conference (90.3% of TC) [15]. A relatively high percentage of tweets (~10%) was published before the conference, in many cases to promote specific sessions of the scientific event or to provide logistic information for attendees.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Of the 1500 public health professionals and students attended the 7 th EPH Conference in Glasgow, only 14% (209 attendees) were us Twitter Contributors (TC) that used #ephglasgow hashtag. In another study the proportion of attendees among TC was similarly high, as reported by Awad and Cocchio in a paper about the use of Twitter at a major national pharmacy conference (90.3% of TC) [15]. A relatively high percentage of tweets (~10%) was published before the conference, in many cases to promote specific sessions of the scientific event or to provide logistic information for attendees.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, all the tweets were categorised as follows, on the basis of previous studies on this topic [13,15,21] The "session-related" tweets were further categorised in six different topics: 1) Health promotion (including advocacy and health literacy);…”
Section: Methodsmentioning
confidence: 99%
“…Ample literature has been published looking at the role of Twitter at various conferences across specialties [19][20][21][22][23][24][25][26]. A tweet analysis of thirteen conferences from 2011-2013 identified 51,159 tweets by 8,778 Twitter account holders of which 25% were identified HCPs who composed 19,503 (38%)of the tweets [19].…”
Section: Social Media Use and Healthcarementioning
confidence: 99%
“…The American Society of Health-System Pharmacists (ASHP) studied Twitter use by attendees of the 2013 ASHP Midyear meeting. 7 More than 400 Twitter accounts from 7 different countries using #ashpmid-year tweeted 1,539 tweets creating 33,116 impressions. Symplur (www.symplur.com), a Web site that provides archiving and analysis of tweets with a hashtag, can generate a transcript of every tweet from a conference to generate future discussions.…”
Section: Director's Forummentioning
confidence: 99%